Politics of grassroots democracy in India - Biju,M.R,Ed; Ravindra Sharma,Ed; Anantha Padmanabha,M.R.B (Concept, 2019)
An attempt has been made in this volume to address the issues pertaining to a wide ranging areas and aspect of the politics of grassroots governments in India viz., administrative process of PR elections, religions and caste influence, structuralfunctional and operational aspects, legal dimensions, political leadership, women leadership, policies and politics of reservation, the right to recall, changing role of the Gram Sabha, linkage between officials and nonofficials, PR elections in selected states, politics of fiscal devolution etc. The chapters are contributed by senior academics, administrators and development experts with rich experience on the core areas of the study. In their submissions, the authors have ride to explore the existing problems and hurdles faced by the grassroots democracy in general and party politics in particular and put forward solid suggestions to revamp the system in its total.